On systems disturbed by wide band noise - Bashirov, AE; Ugural, S (Pergamon-Elsevier Science Ltd, 2002)
In this paper a method of converting a wide band noise driven nonlinear signal-observation system to a white noise driven nonlinear signal-observation system is developed. Copyright (C) 2001 IFAC.
5th IFAC Symposium on Nonlinear Control Systems -- JUL 04-06, 2001 -- ST PETERSBURG, RUSSIA
Keywords: nonlinear systems; wide band noise; white noise; reduction; filtering theory